Energy efficiency, demand side management and energy storage technologies – A critical analysis of possible paths of integration in the built environment. (November 2018) - Tronchin, Lamberto; Manfren, Massimiliano; Nastasi, Benedetto
Abstract: The transition towards energy systems characterized by high share of weather dependent renewable energy sources poses the problem of balancing the mismatch between inflexible production and inelastic demand with appropriate solutions, which should be feasible from the techno-economic as well as from the environmental point of view. Temporal and spatial decoupling of supply and demand is an important element to be considered for the evolution of built environment, especially when creating sectorial level planning strategies and policies. Energy efficiency measures, on-site generation technologies, demand side management and storage systems are reshaping energy infrastructures and energy market, together with innovative business models. Optimal design and operational choices in buildings are systemic, but buildings are also nodes in infrastructural systems and model-based approaches are generally used to guide decision-making processes, at multiple scale. Built environment could represent a suitable intermediate scale of analysis in Multi-Level Perspective planning, collocated among infrastructures and users. Therefore, the spatial and temporal scalability of modelling techniques is analysed, together with the possibility of accommodating multiple stakeholders' perspectives in decision-making, thereby finding synergies across multiple sectors of energy demand. For this reason, the paper investigates first the cross-sectorial role of models in the energy sector, because the use of common principles and techniques could stimulate a rapid development of multi-disciplinary research, aimed at sustainable energy transitions. Further, relevant issues for the integration of energy storage in built environment are described, considering their relationship with energy efficiency measures, on-site generation and demand side management. Highlights: Buildings represent a relevant component in sustainability transition policies. Multi-Level Perspective planning has to be considered in built environment evolution. Analysis of complementarities is crucial to understand technological and sectorial issues. Integration and scalability of computing techniques for optimization and inverse modelling is necessary. Demand side management and storage technologies are essential to decouple production and demand.